«PHENOMENOLOGICAL MOMENT» IN THE DEVELOPMENT OF G.P. MELNIKOV: STATEMENT OF THE PROBLEM - Zagumennov, A.V. (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
The aim of the present article is the experience of constructing the linguistic epistemology of the theoretical developments of G.P. Melnikov in the context of the discussion of the foreign philosophy of science about the influence of E. Husserl’s ideas on structural linguistics. The idea of the article was suggested by the international scientific internship “General and Particular Methodology of Philological Science” from 03.04.2017 to 08.04.2017, as well as some generalizations published in the collective mono-graph “The Systemic View as the Basis of Philological Thought” (2016). Linguistic research methods (description, observation) are transferred to the scientific text as material for the reconstruction of the “phenomenological moment” as a conceptual structure. The article analyzes three lines: the initial internal determinant of the desired construct in the methodology of linguistics, the current external determinant of formal coincidence in some parameters, and the current internal determinant of the evaluation of GP. Melnikov’s own constructions in correlation with a certain epistemological system. The conclusion, which is made in the proposed work, concerns the recognition of G.P. Melnikov, the presence of a phenome-nological moment in the “systemology” he deduced.